Water structure of poly(2-methoxyethyl acrylate) observed by nuclear magnetic resonance spectroscopy. Issue 8 (23rd May 2020) - Mochizuki, Akira; Miwa, Yuko; Yahata, Chie; Ono, Dai; Oda, Yoshinobu; Kawaguchi, Tsubasa
Abstract: Poly(2-methoxyethyl acrylate) (PMEA) is known to show excellent blood compatibility. The performance of PMEA has been attributed to the existence of cold-crystallizable water in it, as observed using differential scanning calorimetry (DSC). However, little is known on the property of the water in PMEA above 0 °C, especially at ambient temperature including the body temperature, because blood compatibility is observed at 37 °C. The present study was performed to clarify the state of water in PMEA in the temperature range 15–45 °C using solution nuclear magnetic resonance spectroscopy (NMR). In addition, water in poly(butyl acrylate) (PBA), which exhibited poor blood compatibility, was used as a control. In the NMR spectra of water in PMEA, two peaks appeared at 4.87 ppm and 3.71 ppm at 30 °C, showing the existence of two types of water structures. The peak intensity of the upfield water was considerably higher than that of the downfield water. On the other hand, the hydrated PBA showed only one peak at 4.98 ppm at 30 °C. The dynamic property of water in these polymers was estimated from the deuterium solution NMR spin-lattice relaxation time, T1 2H . The T1 2H values of peaks observed at 4–5 ppm were relatively high, denoting rapid motion, while those of water at 3.7 ppm in PMEA were small, denoting slow mobility. Thus, the states of water molecules in PMEA in terms of chemical shift and mobility were considered different from those in PBA at ambient temperature.